Aktor dan Konfigurasi Subsistem dalam Perubahan Kebijakan Pengolahan Sampah Menjadi Listrik di Provinsi DKI Jakarta - Sri Utami Gayatri; M. Baiquni; Muhadjir Darwin; Tumiran Tumiran (Populasi, 2018)
Population growth in DKI Jakarta Province continues to increase. The consequence of population increase is indeed in the volume of waste which also continues to increase and at the same time the need for energy is increasing. Since 2011 DKI Provincial Government has implemented waste to energy (WTE) in Bantargebang TPST, but it was not as the main processing unit. Since 2011, DKI Provincial Government has also compiled a plan (2012-2032 Waste Management System Master Plan) to make WTE as a central processing unit by making an Intermediate Treatment Facility (ITF) at four points in DKI Jakarta Province. It was only in 2018, one ITF in Sunter began to be built. To unravel the problem of the slow implementation of RISPS, researcher tried to map the existing network of actors and to explore the extent to which the configuration of the subsystem accepted new ideas and actors in the context of accelerating WTE development. The results of this study indicated that the policy change process runs gradually paradigmatically oriented to policy goals in an open subsystem.